THE EVOLUTION OF PUBLIC REACTIONS ON CELEBRITY GROOMING RELATIONSHIPS: AN ANALYSIS OF BILLIE EILISH AND TAYLOR SWIFT - Tsara, Elka; Susilastuti, Dewi H. (Rubikon : Journal of Transnational American Studies, 2024)
The two well-known female musicians, Billie Eilish and Taylor Swift are examined in connection to their grooming relationships within different periods, specifically in the pre-and post-Me Too movement. The study uses comparative analysis, and feminist media theory was implied, it explores public perceptions, digital magazine portrayal, and cultural awareness of on grooming relationships depicted by celebrities. The pre-Me Too era, characterized by romanticized portrayals of celebrity romances and a shortage of investigation into power dynamics, gave rise to accusations concerning Swift’s grooming relationship. However, when the Me Too movement gained popularity, Eilish made her charge at a period when grooming techniques were more generally acknowledged and denounced. This article highlights how societal perceptions of consent, power dynamics, and ethical problems in relationships have evolved using news reporting, cultural discussions, and public responses. The findings demonstrate how public discourse, along with an understanding of celebrity grooming relationships, has been revolutionized by social movements such as Me Too. In the context of evolving societal norms and values, they also illuminated how the public’s views and media portrayals are shifting.